Tensions and Possibilities: A qualitative study of the views of nurse faculty training medical students to be Health Care Assistants - Patel, Kishan; Gay, Simon; Holland, Richard; Anderson, Elizabeth (International Journal of Practice-based Learning in Health and Social Care, 2023)
In the majority of pre-registration training programmes early theory is supported by later clinical learning. Unlike nursing, midwifery and the allied health professions, medical training often offers relatively little early clinical patient contact, though this does vary by medical school. To overcome this, recently, some medical schools offer patient-facing nurse training for the Care Certificate (CC) in the first year, but as yet little is known about how this is being received by nurses. We report on the experiences and perceptions of nurse-led faculty who led a pilot for first year medical students to gain the CC in the academic year 2019-20, in one UK medical school. The qualitative study involved one-to-one in-depth semi-structured interviews with the course educators. Data were analysed using reflexive thematic analysis. Seven faculty participated, sharing their delight at students’ willingness to embrace the CC. Five main themes arose: i) perceptions of doctors and nurses in the healthcare system; ii) affinity with the medical students; iii) benefits of the CC for medical students working as Health Care Assistants; iv) anxiety about teaching the medical students; and, v) uncertainty about whether this training should be compulsory. We discovered that, nurses yearn for greater appreciation for their work by the medical workforce. These teachers felt this could be realised through this change within first year medical training. Many benefits were perceived as an outcome of this training for medical students, all members of the clinical team and most importantly for patients.